Image_5.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
In the local Marathi dialect, tandula means rice, and bhakri means roti, resulting in the tandalachi bhakri, or rice roti. While the basic preparation method remains the same, there are variations of bhakri made with different flours. These include jowar (sorghum), bajra (pearl millet), and nachni (finger millet), which are common in different regions of India.